Plasmodium vivax Biology: Insights Provided by Genomics, Transcriptomics and Proteomics - Bourgard, Catarina; Albrecht, Letusa; Kayano, Ana C. A. V.; Sunnerhagen, Per; Costa, Fabio T. M. (Frontiers in Cellular and Infection Microbiology, 2018)
During the last decade, the vast omics field has revolutionized biological research, especially the genomics, transcriptomics and proteomics branches, as technological tools become available to the field researcher and allow difficult question-driven studies to be addressed. Parasitology has greatly benefited from next generation sequencing projects, which have resulted in a broadened comprehension of basic parasite molecular biology, ecology and epidemiology. Malariology is one example where application of this technology has greatly contributed to a better understanding of Plasmodium spp. biology and host-parasite interactions. Among the several parasite species that cause human malaria, the neglected Plasmodium vivax presents great research challenges, as in vitro culturing is not yet feasible and therefore functional assays are heavily limited. Therefore, there are gaps in our P. vivax biology knowledge that affect decisions for control policies aiming to eradicate vivax malaria in the near future. In this review, we provide a snapshot of key discoveries already achieved in P. vivax sequencing projects, focusing on developments, hurdles, and limitations currently faced by the research community, as well as perspectives on future vivax malaria research.